Functional and genetic analysis of haplotypic sequence variation at the nicastrin genomic locus. - Hamilton, G; Killick, R; Genetic, A; Translational, G; Lambert, J; Amouyel, P; European, A; Carrasquillo, M; Pankratz, V; Graff-Radford, N; Dickson, D; Petersen, R; et al. (2012)
Nicastrin (NCSTN) is a component of the γ-secretase complex and therefore potentially a candidate risk gene for Alzheimer's disease. Here, we have developed a novel functional genomics methodology to express common locus haplotypes to assess functional differences. DNA recombination was used to engineer 5 bacterial artificial chromosomes (BACs) to each express a different haplotype of the NCSTN locus. Each NCSTN-BAC was delivered to knockout nicastrin (Ncstn(-/-)) cells and clonal NCSTN-BAC(+)/Ncstn(-/-) cell lines were created for functional analyses. We showed that all NCSTN-BAC haplotypes expressed nicastrin protein and rescued γ-secretase activity and amyloid beta (Aβ) production in NCSTN-BAC(+)/Ncstn(-/-) lines. We then showed that genetic variation at the NCSTN locus affected alternative splicing in human postmortem brain tissue. However, there was no robust functional difference between clonal cell lines rescued by each of the 5 different haplotypes. Finally, there was no statistically significant association of NCSTN with disease risk in the 4 cohorts. We therefore conclude that it is unlikely that common variation at the NCSTN locus is a risk factor for Alzheimer's disease. Copyright © 2012 Elsevier Inc. All rights reserved.